Analisis Properti Psikometris pada Instrumen Self-Reported Questionnaire (SRQ)-20 dengan Rasch Model - Prahastuti, Nurul Fajriyah (INSAN Jurnal Psikologi dan Kesehatan Mental, 2023)
Screening instruments for mental disorders is useful for society in identifying the possibility of mental disorders in themselves or others. Screening instruments are tools used to examine early symptoms of mental disorders, early detection, intervention for mental disorders, as well as research. The Self-Reported Questionnaire-20 (SRQ-20) is an instrument for screening mental disorders through individual assessment. This study aims to determine the quality of SRQ-20 instrument using Rasch model analysis techniques with the assistance of Jamovi software version 2.3.18.0. The participants in this study were individuals aged 12 – 44 years. The number of participants was 165. The instrument used was SRQ-20 with a total of 20 items. The results of the study showed that all 20 items met the item-model fit. The reliability coefficient value was 0.823. Overall, SRQ-20 has good psychometric properties.